Possibilities and limitations of teledentistry - Dmitry E Suetenkov; Olga V Popkova; Anton R Kiselev (Editorial Ciencias Médicas, 2020)
Dental care is considered to be an example of complex manual interventions in the medical sector. The vision presented describes the organization of dental care based on the application of modern telecommunication technologies. In developed countries, general dental practitioners have a positive attitude toward incorporating teledentistry into their practice. In PubMed there is a tendency to increase the states by telehealth key words and tags, including teledentistry. Those health care tendencies show a steady trend toward the broadening of teledentistry services.